Effect of computer-aided design/computer-aided manufacturing bleach shade ceramic thickness on its light transmittance and microhardness of light-cured resin cement - Pardis Sheibani; Ghazaleh Ahmadizenous; Behnaz Esmaeili; Ali Bijani (Wolters Kluwer Medknow Publications, 2024)
Background: This study aimed to measure light transmittance (LT) through various thicknesses of computer-aided design/computer-aided manufacturing bleach shade ceramics and to assess the Vickers microhardness (VMH) of underlying light-cured resin cement. Materials and Methods: In this in vitro study, a total of 90 ceramic discs (VITA Mark II [VM], VITA Suprinity, and CELTRA Duo) were prepared in 0.5, 1, and 1.5 mm thicknesses. To measure LT, the Valo light-curing unit was placed in direct contact with the ceramics on the radiometer. The average LT was recorded after three measurements. In addition, 90 specimens of light-cured resin cement (Allcem Veneer) were cured in Teflon molds (0.5 mm in depth) beneath ceramic pieces. Ten specimens of resin cement were also cured without the presence of ceramic as a control group. VMH of the cement specimens was reported. The data were analyzed by one-way analysis of variance and multiple comparison tests (α =0.05) in SPSS version 17. Results: In each ceramic group, LT was negatively related to ceramic thickness (P < 0.05). At a thickness of 1.5 mm among all ceramic types, the VMH of resin cement was significantly decreased (P < 0.05). In all thicknesses, the VMH of resin cement was lower significantly than the control group, except for the thickness of 0.5 mm of VM. Conclusion: According to the results of this study, light-cured cement is not a suitable option for cementing the studied bleach shade ceramics. Furthermore, the thickness of the ceramic has a significant effect on LT (P < 0.05), unlike VMH.